2015
DOI: 10.1017/s1047951114002728
|View full text |Cite
|
Sign up to set email alerts
|

The impact of illness perceptions and disease severity on quality of life in congenital heart disease

Abstract: Symptoms of depression and anxiety are common among adults with CHD. Patients' illness perceptions are related to psychological outcomes, especially cross-sectionally. Future research could investigate whether an intervention to discuss patients' perceptions about their CHD can improve mental health and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 34 publications
4
29
0
Order By: Relevance
“…Nevertheless, given the nature of our cross-sectional study, we cannot determine the direction of the relationship, namely whether poor HRQOL leads to worse perceptions or that worse perceptions leads to poor HRQOL domain scores. Consistent with our results, O’Donovan et al have shown that, in a cohort of patients with congenital heart disease, illness perceptions were also predictive of different HRQOL domains and psychological outcomes, including depression and anxiety [51]. …”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, given the nature of our cross-sectional study, we cannot determine the direction of the relationship, namely whether poor HRQOL leads to worse perceptions or that worse perceptions leads to poor HRQOL domain scores. Consistent with our results, O’Donovan et al have shown that, in a cohort of patients with congenital heart disease, illness perceptions were also predictive of different HRQOL domains and psychological outcomes, including depression and anxiety [51]. …”
Section: Discussionsupporting
confidence: 91%
“…The role of underlying anxiety or depressive symptoms in the development of illness perceptions and assessment of QOL must be acknowledged, especially as internalizing symptoms are frequently elevated among patients with complex CHD. 7,10,15 To address this issue, we controlled for anxiety and depressive symptoms in the mediational analyses. Therefore, illness perceptions were less influenced by underlying psychological symptoms and were more likely to reflect independent CHD-related beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…First, all data were cross-sectional; the ability to determine whether illness perceptions predicted QOL over time was not possible, although current literature suggests that illness perceptions may predict future QOL in adults with CHD. 14,15 Second, the internal consistency of the illness perceptions composite was slightly less than the standard 0.70, although the decision was made to retain the variable due to the relative lack of knowledge regarding illness perceptions in CHD. One possibility is that the greater perceived treatment benefits reported by…”
Section: Imit At Ionsmentioning
confidence: 99%
“…[86][87][88] Psychosocial morbidities in the ACHD population include an increased prevalence of anxiety, depression, and posttraumatic stress disorder. [89][90][91] The recent recognition of ACHD medicine as a distinct subspecialty of cardiology by the American Board of Internal Medicine establishes the importance of appropriate training in the care of this challenging patient population. 92 The future of this field is likely to see further growth in a team-based approach to their management, centers of excellence for their care, and attention to their mental health, employability, and social relationships.…”
Section: Adults With Chdmentioning
confidence: 99%